A influência do espaço social na sobrecarga de mulheres cuidadoras de crianças com cuidados contínuos e complexos - Buboltz, Fernanda Luisa (2019)
Care for children with continuous and complex care requires significant changes in the dynamics of families. This condition ends up generating an overload on the main caregiver, who usually focuses on the figure of the woman. This study aimed to analyze the influence of social space on the overload of women caregivers of children with continuous and complex care. Specific objectives: characterize the overload, the health profile and the sociodemographic profile of women caregivers of children with continuous and complex care; characterize the clinical profile of children with continuous and complex care; to grasp and interpret the influence of social space on the overload of women caregivers of children with continuous and complex care. The philosophical theoretical reference, conducting the study, consisted of the references of Bourdieu. Mixed method research, sequential explanatory type with women caregivers of children with continuous and complex care. The study scenario - in the quantitative phase - consisted of the pediatric units of the University Hospital of Santa Maria, the Association of Parents and Friends of the Exceptional of Santa Maria / RS; in the qualitative phase, the scenario consisted of the domiciles of women caregivers of these children who participated in the quantitative phase. The data collection was performed through a scale, a sociodemographic questionnaire and the health of the female caregiver and a clinical profile of the child in the quantitative phase. In the qualitative phase, semi- structured interviews were carried out from August 2017 to February 2018. Quantitative data analysis was performed using the "R" program, using descriptive and analytical statistics. The qualitative data were analyzed from the assumptions of Pechetiana discourse analysis. Ethical aspects were respected in accordance with Resolution 466/2012 of the National Health Council. The results of the study indicated that 50.6% (N = 42) of women caregivers of children with continuous and complex care presented an average overload to moderate. There was a significant difference between the overload scores of women who care for children with developmental demands. Moreover, the overload of women carers of these children is strongly influenced by the Social Space, in a polarized way, by the social, cultural and economic capitals. In this space, the woman, from her habitus, fights for her rights and her child according to the offer or not of these capitals. These women are victims of symbolic violence, which presents itself in a variety of ways in Social Space such as male domination, the myth of maternal love, prejudice and stigma that permeate the daily life of the child with continuous and complex care. It is recommended that health professionals, in a multiprofessional way, develop therapeutic plans for these women, considering that they are inserted in a Social Space that influences all their actions and interferes in their health and that of the child with continuous and complex care.